ENVIRONMENTAL MEDICINE IN RELATION TO RURAL HEALTH - mansour mohammadian (Tehran University of Medical Sciences, 1975)
The health of the world rural community has become the focus of attention during the past several years. Realizing the future of the traditional system of medical practice many countries have initiated specific public health programmes in order to alleviate the plight of this group of people. However, in their effort to establish such programmes the medical community must not be oblivious of that all important facet of rural life, that is their environment, both physical and socio-cultural, in which these people live and work. This is because the group of diseases which most affect the rural community are very often induced by environmental causes rather than pathogenic agents. This class of diseases constitutes the field of environmental human medicine and drawing upon the experiences gained in the field of environmental veterinary medicine, medical practitioners should be in a better position to affect public health measures in rural areas where envionment still exerts a significant role in the health status of the community. The advantages of an effective treatment of these endemic, environmental diseases as a group should he abvious for the rural community and also for increasing food production by improving livestock productivity and preventing waste. A research model for determining the concepts and techniques of dealing with these diseases as a group is proposed. Rural health is, to a great extent, governed by a group of diseases which are due more to environmental causes than specific pathogenic agents. The treatment of each individual endemic disease on its own will not really solve the problem of rural health nor will it lead to any significant improvement in the health status of the rural community. Therefore, these endemic environmental.